Influence of the Landscape Template on Chemical and Physical Habitat for Brown Trout Within a Boreal Stream Network - Buffam, Ishi; Bishop, Kevin; Laudon, Hjalmar (Frontiers in Water, 2021)
We used the distribution of stream-dwelling brown trout (Salmo trutta) in a meso-scale (67 km2) boreal stream network to explore the importance of environmental organizing factors at a range of spatial scales, including whole-catchment characteristics derived from map data and stream reach chemical and physical characteristics. Brown trout exhibited a threshold response to pH and were not observed at any sites characterized by pH <5.0 during the spring snowmelt episode, matching published toxicity thresholds. Brown trout distributions were patchy even in less acidic regions of the stream network, positively associated with glaciofluvial substrate and negatively associated with fine sand/silty sediments. A multivariate model including only whole-catchment characteristics explained 43% of the variation in brown trout densities, while models with local site physical habitat characteristics or local stream chemistry explained 33% and 25%, respectively. Most of the correlation between whole-catchment characteristics and trout distributions could be attributed to effects mediated by site physical and stream chemistry characteristics. Physical habitat apparently played a primary role in organizing brown trout distributions in this stream network, with acidity placing an additional restriction by limiting brown trout in acidic headwater streams. These results, consistent with the concept of multiple hierarchical environmental filters regulating the distribution of this fish species, underline the importance of considering a range of spatial scales and both physical and chemical environments when attempting to restore streams for brown trout.